Textile design - Clarke, Simon, 1963- (Laurence King, 2011)
Textile design has a very exciting future. New fibres, fabrics and applications are constantly appearing and designers now have a wealth of avenues to explore. This book offers students a basic grounding in the three main pathways of textile design printed, woven and mixed media textile design
Terminologický slovník
Keywords: textilní design; textilie; textilní techniky; textile design; textile fabrics; textile techniques; učebnice; textbooks